Linewidth of Short External Cavity Semiconductor Lasers - Woodside, Shane (My University, 1992)
This thesis describes the development of a technique for measuring frequency noise of semiconductor lasers. Equivalent laser linewidths were calculated from frequency noise measurements on several InGaAsP lasers with short external cavities to give single mode operation. Conventional 250 um lasers demonstrated linewidths of about 125 MHz-mW, compressively strained quantum well lasers of commensurate length had linewidth of 37 MHz-mW, and 500 um strained quantum well lasers had linewidth of 18 to 28 MHz-mW with an apparent strain dependence. The short external configuration allowed selection of a number of laser modes. Measurement of linewidth variation with laser mode showed a 20% to 40% change over six to eight modes. The system was adapted to make measurements of the optical frequency tuning with fine external cavity length change. This measurement provided a novel means to estimate the linewidth enhancement factor and the reflectivity of the external cavity element. The estimated values of the linewidth enhancement factor for 250 um conventional and quantum well lasers were found to be in the correct ratio to account for the measured difference in linewidth.
Keywords: short external cavity; semiconductor lasers